Potencialidades e desafios de um aeroporto para transporte aéreo de carga na mesorregião oeste potiguar - Alves, Marcelo Romell Nunes (Universidade Federal Rural do Semi-Árido, 2019)
The use and modernization of the air modal is in growing development, but currently still presents low use when compared to other modal. This type of transport offers advantages such as speed of delivery, greater care of loads due to strict quality control, low accident and theft rate, access to distant areas, which direct access by sea or road is not possible. Although it presents many advantages, the main limiting factor to its use is the high cost, being more used for products with greater added value, since it also has limitation as to the load capacity, rendering unviable the transport of loads in bulk. The objective of this study was to identify the existing potential in the state of Rio Grande do Norte (RN), and the challenges presented by them for the feasibility of implementing or adapting an airport for air cargo transportation in the western mesoregion of the state. Currently, there are 2 airports in the RN, one of them located in the eastern mesoregion, which carries out national and international flights, for passenger and cargo transportation, with a modern infrastructure. The other is located in the western mesoregion and has been deactivated for seven years, having been reactivated in 2018, with only simple flights, from Mossoró to Recife. Data on productivity, sales and exports, which were characterized as potential for the air transport of cargoes, were investigated and identified the challenges presented by them. It was verified that the state has potential in some sectors, such as textiles and clothing, livestock, and especially in fruit growing, some products produced in the region with nationally and internationally recognized quality. However, it was concluded that the productive volume of the state, coupled with current demand, is still insufficient to justify such an investment, lacking public and private investments and initiatives that value production in the state. In this way, it was suggested actions and investments that can be made for the development and use of this potential in the future, making possible the implantation of the airport.
Monografia
Keywords: Rio Grande do Norte; Potencial para transporte de cargas; Produtos da região; Rio Grande do Norte; Potential for cargo transportation; Products from the region; ENGENHARIAS::ENGENHARIA DE PRODUCAO